DIFFERENCES IN SOME ANTHROPOLOGICAL DIMENSIONS BETWEEN 11 - 13 YEAR OLD ATHLETE BOYS AND NON-ATHLETE BOYS - Adi Mujičić,; Edin Užičanin,; Vlatko Separović,; Fuad Babajić, (Sport Scientific And Practical Aspects, 2025)
The main aim of this research was to determine the differences between 11 to 13 year old athletes and non-athletes. The study was conducted on a sample of 110 boys aged 11.7 ± 2.5, divided into two sub-categories: The first sub- sample of 50 boys - athletes (body height: 153.6 ± 9.9, body weight: 46, 3 ± 10.6, body fat percentage: 15.9 ± 7.9), who in addition to regular physical education classes had additional physical activities, i.e. were the basketball school attendees. The program was realized from April to September (six months), twice a week for 1.5 hours. The second sub-sample of 60 non-athlete boys, (body height: 152.3 ± 7.9, body weight: 46.1 ± 10.3, body fat percentage: 15.9± 6.6), who had regular physical education classes but have not had any additional organized physical activity. T-test results for the independent samples showed a significant difference between athletes and non-athletes in two applied tests: MAGTUP - running in a rectangle and MFESDM - long distance jump in favor of athletes.